Teladorsagia circumcincta beta tubulin: the presence of the E198L polymorphism on its own is associated with benzimidazole resistance - Martínez-Valladares, María (Parasit Vectors, 2020)
BACKGROUND: Benzimidazole resistance is associated with isotype-1 β-tubulin gene F200Y, E198A and F167Y SNPs. In this study, the recently described polymorphism E198L was reported and analysed in Teladorsagia circumcincta. METHODS: The benzimidazole phenotypic resistance was measured by the faecal egg count reduction test (FECRT) and the egg hatch test (EHT) using a discriminating dose (DD) in 39 sheep flocks. Around 1000 larvae collected before and after treatment were used for DNA extraction. The resistant species identified in all flocks was T. circumcincta. The resistance alleles frequencies were measured for F200Y and E198A. A 371-bp fragment of the isotype-1 β-tubulin gene was analysed, including the three codons of interest, and a new pyrosequencing assay was designed for testing E198L. RESULTS: The percentage of resistant flocks was 35% by FECRT or 26% by EHT; however, F200Y and E198A SNPs were absent in T. circumcincta. The amplification of a 371-bp fragment confirmed the absence of F167Y and F200Y in 6 resistant flocks. Regarding codon 198, all samples after treatment carried a leucine (CTA). A pyrosequencing assay analysed the allele frequencies for the first two bases at codon 198 independently, G/C and A/T. The correlation between C and T frequencies was almost 1 (r = 0.929, P < 0.0001) and the mean value of both was calculated to measure the leucine frequency; this value ranged between 10.4–80.7% before treatment, and 82.3–92.8% after treatment. High and similar correlations were reported between the genotypic variables (C frequency, T frequency or mean of both frequencies) and phenotypic resistance (r > 0.720, P < 0.0001), although negatively associated with the FECRT and positively with the EHT. According to multivariate linear regression analysis, the T frequency was the most significant variable influencing the phenotypic resistance (FECRT or EHT; P < 0.0001). In the EHT, 67.1% of the phenotypic variability is associated with the T frequency but in the FECRT only 33.4%; therefore, the EHT using a DD seems to detect the genotypic resistance more accurately than the FECRT. CONCLUSIONS: The E198L polymorphism can confer BZ resistance on its own in T. circumcincta. [Image: see text]